Biocomposites from the reinforcement of a tung oil-based thermosetting resin with collagen. (11th May 2017) - Scholz, Audrey; Lewis, Russell L.; Bachan, Michael A.; Stewart, Amanda L.; Quirino, Rafael L.
Abstract : Collagen from three different sources has been added to a tung oil-based thermosetting resin in order to enhance its mechanical properties for possible applications in the biomedical field as materials directly derived from biological molecules. Abstract : Collagen from three different sources has been added to a tung oil-based thermosetting resin in order to enhance its mechanical properties for possible applications in the biomedical field as materials directly derived from biological molecules. The thermosets prepared in this work are made using tung oil, divinylbenzene (DVB), n -butyl methacrylate (BMA), tert -butyl peroxide (TBPO), asolectin, and collagen types I and III. Composites containing up to 5.0 wt% of collagen have been successfully prepared and characterized by dielectric analysis (DEA), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The structure of the collagen samples used in this work was investigated through circular dichroism (CD) spectroscopy. Dynamic mechanical analysis (DMA) was used to assess composites' mechanical properties and revealed an improvement in the storage modulus at room temperature with increasing amounts of collagen, reaching an impressive increase of ∼100% for composites containing 5.0 wt% of collagen extracted from beef tendons in comparison to the unreinforced resin. The results indicate that collagen exhibits a reinforcing behavior similar to that obtained with nanostructured materials, such as carbon nanotubes for instance, therefore working as an effective reinforcement for the preparation of biocomposites.